1996
DOI: 10.1177/000331979604700214
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Fistula to Bronchial Artery on Contralateral Side of Coronary Atherosclerosis and Myocardial Insufficiency

Abstract: Among coronary vessels anomalies is the rare coronary artery fistula. Myocardial insufficiency resulting from fistula steal phenomenon can not be clinically distinguished from that of coronary atherosclerosis, if these conditions coexists in the same patient. The authors present a case of extracardiac left coronary artery fistula connecting the circumflex branch and left bronchial artery, with inferior wall myocardial insufficiency attributable to the right coronary artery atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…CBFs may have a unilateral [7, 8] or bilateral [9] presentation. As early as 1803, a Cx coronary artery to right bronchial artery communication was initially described by von Haller [10].…”
Section: Discussionmentioning
confidence: 99%
“…CBFs may have a unilateral [7, 8] or bilateral [9] presentation. As early as 1803, a Cx coronary artery to right bronchial artery communication was initially described by von Haller [10].…”
Section: Discussionmentioning
confidence: 99%
“…A coronary-bronchial artery fistula is a rare congenital anomaly that occurs at the coronary artery [1]. It has been reported that this anomaly is detected in 0.18% of patients who undergo coronary angiography [2].…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite their rarity, a subset of patients may develop severe complications, including heart failure, ischemia, and arrhythmias. Notably, approximately 30% of adult cases of CAF are associated with coronary atherosclerosis, 3 to occur as distinct and independent phenomena, as illustrated in the case reported by Wandwi et al, 6 and in another case by Brunetti et al, 7 where occlusions in the left circumflex and right coronary arteries coexisted with a fistula connecting the left main and diagonal branch, draining into the pulmonary artery, without apparent interrelation. Conversely, there are instances where CAF and coronary atherosclerosis coexist within the same coronary artery, suggesting a potential interconnection between these two conditions.…”
Section: Discussionmentioning
confidence: 95%